2008
DOI: 10.21608/jhiph.2008.20873
|View full text |Cite
|
Sign up to set email alerts
|

Needle Stick Injuries among Health Care Workers of Alexandria University Hospitals

Abstract: Background: Needle stick injury has been recognized as one of the occupational hazards which results in transmission of blood borne pathogens. As there was limited data on the national level about these injuries determinants of such injuries are important to investigate and to design effective prevention programs. Objective: The purpose of this study was to investigate the prevalence and circumstances of needle stick injuries among heath care personnel working at Alexandria University hospitals. Effectiveness … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
12
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(18 citation statements)
references
References 9 publications
6
12
0
Order By: Relevance
“…In this study, the majority of HCWs who sustained needle stick and sharp injury were Nurses. It is in agreement with a study done in Egypt, 16 and it is much higher as compared to studies done in Switzerland, South Africa, SSA, Nigeria, and Saudi Arabia. [9][10]15,[18][19] The possible difference may be due to the job description given to nurses where in Ethiopia a lot of exposure-prone procedures such as medication administration, and wound care are handled by nurses.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…In this study, the majority of HCWs who sustained needle stick and sharp injury were Nurses. It is in agreement with a study done in Egypt, 16 and it is much higher as compared to studies done in Switzerland, South Africa, SSA, Nigeria, and Saudi Arabia. [9][10]15,[18][19] The possible difference may be due to the job description given to nurses where in Ethiopia a lot of exposure-prone procedures such as medication administration, and wound care are handled by nurses.…”
Section: Discussionsupporting
confidence: 92%
“…The study is almost in agreement to a study done in Egypt. 16 Implying that HCWs might practice recapping and/or might dispose of needles inappropriately. In the study area the practice of needle recapping after use is still prevalent among HCWs, where almost three fourths of the respondents (74.7%) reported that they were recapping the needles immediately after use, and from them one third (34.7%) were recapping using two hand technique.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Exposure to blood and body fluids remains an important concern for healthcare workers, especially those who sustain a percutaneous injury. The risk of acquiring hepatitis B infection following a needle stick injury is estimated at approximately 30% [27].…”
Section: Discussionmentioning
confidence: 99%
“…-Nurses were asked to fill out the questionnaire sheet (tool I) to assess nurses` awareness and knowledge completely and truthfully. Nurses spent (10)(11)(12)(13)(14)(15) (23) was used to analyze data. Descriptive statistics was used for the quantitative data in knowledge and awareness questionnaire and the demographic data.…”
Section: Subject and Methodsmentioning
confidence: 99%